(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: This study investigates the biochemical and spectroscopic alterations in mice brain after blast traumatic brain injury (bTBI), focusing on molecular alterations detected by Fourier Transform Infrared (FTIR) spectroscopy. Methods: Male and female Balb/c mice were subjected to blast traumatic brain injury (bTBI) using an improvised explosive device (IED). Neurological impairment, neurobehavioral deficits, metabolic changes, brain water content, infarct size, and antioxidant enzyme activity were assessed to characterize the TBI- induced alterations. FTIR spectroscopy was employed to analyze the molecular composition of the brain and liver tissues. Results: The Neurological Severity Scores (NSS) revealed varying degrees of injury, with mild, moderate, or severe impairment. Neurobehavioral assessments using open field, beam walk, and elevated plus maze tests demonstrated altered exploratory behavior and anxiety-related behavior deficits in TBI mice. The metabolic assessment revealed changes in body weight, blood count, and blood glucose levels. Brain water content measurement and infarct size estimation indicated the presence of cerebral edema and tissue damage after bTBI. Assessment of antioxidant enzyme activity revealed altered levels of catalase, glutathione, superoxide dismutase, and nitrate in the brain, suggesting oxidative stress and inflammation. Furthermore, FTIR spectroscopy analysis provided insights into the molecular alterations that occur in the brain and liver homogenate after bTBI. Conclusion: This study highlights the critical role of oxidative stress in the pathophysiology of bTBI and demonstrates that FTIR spectroscopy is a promising method for detecting biochemical alterations in brain and liver. These findings may contribute to the development of more sensitive diagnostic approaches and therapeutic strategies for blast-induced brain injury.